The influence of University brand equity, offering equity, and relationship equity on customer satisfaction and customer loyalty: case study in the master of management program, Faculty of Economics, Bakrie University - Yuliandari Cahyaningtyas; Jerry Heikal (Sean Institute, 2024)
Competition for postgraduate study programs in Indonesia is quite high. In fact, it is not only professionals who are interested in attending this university, but also many fresh graduates who then choose to continue their studies. The Master of Management Program at the Faculty of Economics, Bakrie University is one of the study programs that receives high interest from prospective students. To be able to compete with various universities, both on a national and international scale, an evaluation of the performance of the programs that have been implemented so far is needed. Research methods This use method quantitative with use tool AMOS SEM analysis . The sample in this study was selected by applying a purposive sampling technique which involves selecting elements in the sample for a specific purpose with amount sample as many as 86 respondents . Result of study ie Student customer satisfaction has a significant positive effect on student customer loyalty. To increase customer loyalty of students in the Master of Management Program, Faculty of Economics, Bakrie University, it is recommended to strengthen the quality of the arrangement of rooms and equipment by focusing on the arrangement of rooms and equipment which is considered very satisfactory, as an indicator of customer satisfaction with the highest average value. = 8.71).